Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d2sc01934e
|View full text |Cite
|
Sign up to set email alerts
|

A peptide-derived strategy for specifically targeting the mitochondria and ER of cancer cells: a new approach in fighting cancer

Abstract: An effective anti-cancer therapy should exclusively target cancer cells and trigger in them a broad spectrum of cell death pathways that will prevent avoidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 84 publications
(208 reference statements)
2
25
0
Order By: Relevance
“…NAF-1 44–67 has significant medical promise. It selectively permeates the plasma membrane of malignant but not normal cells . Once it has penetrated the plasma membrane, it also traffics to specific organelles, targeting the MIT and ER but not the nuclear membrane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAF-1 44–67 has significant medical promise. It selectively permeates the plasma membrane of malignant but not normal cells . Once it has penetrated the plasma membrane, it also traffics to specific organelles, targeting the MIT and ER but not the nuclear membrane.…”
Section: Introductionmentioning
confidence: 99%
“…It selectively permeates the plasma membrane of malignant but not normal cells. 23 Once it has penetrated the plasma membrane, it also traffics to specific organelles, targeting the MIT and ER but not the nuclear membrane. This remarkable selectivity is further enhanced by the ability of the peptide to kill cancer cells by itself, without carrying additional therapeutic cargo and without damaging normal cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, we have used both experiment and theory to examine the process of small molecule translocation across model membranes. We previously studied the influence of charge on permeation of the amino acid tryptophan into large, unilamellar vesicles (LUVs) composed of 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) by changing the protonation state on the N- or C-terminus using solution pH. Both experiments and complementary molecular dynamics (MD) simulations revealed that permeation is more favorable for positively charged peptides with ∼10 8 fold more positively charged tryptophan (Trp+) partitioning into the membrane than zwitterionic and negatively charged tryptophan (Trp-), and a lower potential mean force barrier for Trp+ compared to Trp–.…”
Section: Introductionmentioning
confidence: 99%
“…However, other positively charged residues (e.g., lysine) play a similar role. Lys was chosen over Arg because it is relevant to recent work from our laboratories. , While WKW is more positively charged than Trp+, it was not more successful in membrane permeation, requiring elevated temperatures to promote any partitioning into the lipid bilayer. Using MD simulations, we proposed a defect-assisted permeation mechanism for WKW with the local free energy minima of the peptide situated in the plane of either membrane leaflet with its positive charges interacting with the lipid phosphate groups and tryptophan side chains protruding into more hydrophobic regions of the bilayer.…”
Section: Introductionmentioning
confidence: 99%